2021
DOI: 10.3390/toxins13040290
|View full text |Cite
|
Sign up to set email alerts
|

Short Linear Motifs Characterizing Snake Venom and Mammalian Phospholipases A2

Abstract: Snake venom phospholipases A2 (PLA2s) have sequences and structures very similar to those of mammalian group I and II secretory PLA2s, but they possess many toxic properties, ranging from the inhibition of coagulation to the blockage of nerve transmission, and the induction of muscle necrosis. The biological properties of these proteins are not only due to their enzymatic activity, but also to protein–protein interactions which are still unidentified. Here, we compare sequence alignments of snake venom and mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…Over 200 nonredundant, complete, and reviewed sequences of svPLA 2 s can be found in the UniProtKB Database (accessed in March) . Their primary structure shows a significant percentage of sequence identity among species, and the X-ray structures deposited in the Protein Data Bank (PDB) (e.g., snake venoms, humans, and bovines) revealed that svPLA 2 groups have a markedly similar architecture. ,,, A sequence alignment denoting the conservation of the catalytic center of different species of secreted PLA 2 is shown in Figure , and a sequence identity matrix is presented in Supporting Information (SI), Table S1.…”
Section: The Structure Of Svpla2smentioning
confidence: 99%
See 3 more Smart Citations
“…Over 200 nonredundant, complete, and reviewed sequences of svPLA 2 s can be found in the UniProtKB Database (accessed in March) . Their primary structure shows a significant percentage of sequence identity among species, and the X-ray structures deposited in the Protein Data Bank (PDB) (e.g., snake venoms, humans, and bovines) revealed that svPLA 2 groups have a markedly similar architecture. ,,, A sequence alignment denoting the conservation of the catalytic center of different species of secreted PLA 2 is shown in Figure , and a sequence identity matrix is presented in Supporting Information (SI), Table S1.…”
Section: The Structure Of Svpla2smentioning
confidence: 99%
“…This loop is followed by the second α-helix (α2), which binds to antiparallel β-sheets cross-linked by disulfide bonds (β-wing region). Following this region is the α-helix 3 (α3), which binds to an exceptionally flexible region, the C-terminal loop, that is believed to be involved in the biological effects of these toxins , and allows it to change its conformation and interact with natural lipids. , The crystal structures of svPLA 2 -GIA from the Chinese cobra ( Naja atra ) and svPLA 2 -GIIA from the Indian saw-scaled viper ( Echis carinatus ) venom were used to illustrate these structural characteristics (Figure ). In addition, structures of bovine pancreatic and human synovial PLA 2 are also shown (SI, Figure S1) to emphasize the above-mentioned similar architecture.…”
Section: The Structure Of Svpla2smentioning
confidence: 99%
See 2 more Smart Citations
“…By comparing the sequence of sPLA2s from snake venom with the corresponding human homologues, differences emerged in the short linear motifs (SLiMs) conserved in the two protein categories. This comparison showed that human proteins differ from animal venom in the presence of SLiMs susceptible to undergoing PTMs by the S/T kinases CDK, GSK3, PKA, MAPK, by tyrosine kinases, and by Pin1, a [ST] phosphorylation-regulated prolyl isomerase [ 62 ]. These differences in the sites subjected to PTMs may give the toxins the possibility of establishing different molecular interactions than mammalian sPLA2s and/or confer different resistance to degradative processes via the ubiquitin-proteasome pathway or micro autophagy.…”
Section: Spla2 Activity Can Be Controlled By Post Translational Modif...mentioning
confidence: 99%